Conservation-relevant plant species indicate arthropod richness across trophic levels: Habitat quality is more important than habitat amount. (April 2023) - Tobisch, Cynthia; Rojas-Botero, Sandra; Uhler, Johannes; Kollmann, Johannes; Müller, Jörg; Moning, Christoph; Redlich, Sarah; Steffan-Dewenter, Ingolf; Benjamin, Caryl; Englmeier, Jana; Fricke, Ute; Ganuza, Cristina; et al.
Highlights: Arthropod richness is strongly determined by plant richness indicating protected habitats. Number of red-listed plant species best predicts red-listed arthropod richness. Plant richness is more relevant for most arthropod groups than habitat amount. Semi-natural habitats and edge density promote conservation-relevant plant species. Abstract: The massive declines in terrestrial arthropods reported across Europe call for effective methods to monitor and promote biodiversity in human-dominated landscapes. Previous studies vary in their support for the suitability of plants as indicators of arthropod diversity, while the potential of subsets of conservation-relevant plant species to estimate arthropod richness remains to be tested. Moreover, the relative importance of plant species richness compared to other factors driving arthropod richness, such as land-use intensity, habitat amount and landscape configuration, is poorly understood. We conducted a multi-scale field study in Southern Germany, sampling vascular plants and terrestrial arthropods in four local land-use types (forest, grassland, arable field, settlement) across large-scale gradients of climate and land-use intensity. We obtained an extensive arthropod dataset using Malaise traps as sampling method and DNA metabarcoding for species identification. We compared the correlation of three sets of plant species richness (total, red-listed and biotope-indicator plants) with arthropod richness, including different trophic and taxonomic groups. Using mixed-effect models, we assessed the partial effects of plant species richness, habitat amount and landscape configuration on local arthropod richness while controlling for climate and land-use effects, and explored the environmental drivers of plant species richness. Arthropod species numbers of all trophic groups strongly responded to species numbers of plants that indicate protected habitats, while red-listed plant species richness was a key determinant for the richness of red-listed arthropods and butterflies. In most cases, plant species richness and temperature were stronger drivers of arthropod richness than the amount of surrounding semi-natural habitat and landscape configuration. While total plant species richness was highest in settlements, the richness of biotope-indicator plants was highest in forests and positively influenced by the amount of semi-natural habitat and edge density. The number of red-listed plant species increased with edge density at the landscape scale but was independent of habitat amount. We conclude that the richness of conservation-relevant plant species provides a powerful indicator of arthropod diversity, and underpins the potential of such plant lists for monitoring habitat quality. Our study highlights the importance of openings in forests for conservation of plants and arthropods as well as of preserving and restoring fragments of high-quality biotopes in agricultural and urban areas where the amount of semi-natural habitat is limited.